Experiment and Application of Market-Based Control for Engineering Structures - Gang Li; Wen Wang; Hong-Nan Li (Journal of Applied Mathematics)
An experimental study on the vibration control of a single-degree-of-freedom model is carried out to verify market-based control (MBC) strategy effect. Results show that the MBC strategy can reduce both displacement and acceleration responses. Additionally, the MBC strategy is applied to a long-span bridge considering the travelling wave effect. Numerical simulations indicate that the displacement and acceleration responses of the long-span bridge with the travelling wave effect are smaller than those without, and the larger the velocity of travelling wave is, the better the control effect of MBC is. Based on the MBC theory and multimarket-based control (MMBC) presented here it is further applied to a large-space structure considering multiple dimensional features of structural model and ground motions. It is concluded that the MMBC strategy reduces the displacement response of the large-space structure, especially on vertical displacements, but has limited control effects on accelerations.